Electrohydraulic Active Suspension Fuzzy-Neural Based Control System - Jamett-Dominguez, M (IEEE Computer Society, 2018)
A design of a new controller via a combination of fuzzy controller and artificial neural network (ANN) force tracking solution for a full vehicle suspension system with nonlinear electrohydraulic actuator dynamics is proposed. The comparison between the new Fuzzy-ANN force tracking controller designed with passive suspension system and PID-ANN controller previously developed is presented. Simulations and results obtained show that the Fuzzy-ANN combined controller can improve the stability problems caused by disturbances and road conditions, providing a superior passenger comfort. © 2018 IEEE.